Perencanaan keuangan pada “Live Streaming Agency” di PT Check Out Time (COT) - Angga Adriano Falasifa; Edi Hamdi; Dimas Negoro; Muhammad Iskandar (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to develop short-, medium-, and long-term financial planning for PT Check Out Time (COT), a live streaming agency operating in the e-commerce sector. The research method uses a quantitative descriptive approach, processing primary data in the form of planned revenues, costs, investments, and capital requirements, as well as secondary data from industry reports and related literature. The analysis was conducted through financial statement projections (profit and loss, balance sheet, cash flow), investment feasibility analysis using ROI, NPV, IRR, and Payback Period methods, and financial ratio analysis (liquidity, solvency, and profitability). The results indicate that PT COT has positive financial prospects, with projected revenue growth annually, an ROI of 35%, an NPV of IDR 45.97 billion, an IRR of 48%, and a payback period of approximately 3 years and 11 months. Financial ratios also indicate strong liquidity, healthy solvency, and increasing profitability since the third year. In conclusion, investing in PT COT is deemed feasible and profitable, and capable of supporting the company's long-term growth strategy to expand its market and increase its competitiveness in the e-commerce live streaming industry.